Immunological and inflammatory profiles in mild and severe cases of COVID-19 - Song, Jin-Wen; Zhang, Chao; Fan, Xing; Meng, Fan-Ping; Xu, Zhe; Xia, Peng; Cao, Wen-Jing; Yang, Tao; Dai, Xiao-Peng; Wang, Si-Yu; Xu, Ruo-Nan; Jiang, Tian-Jun; et al. (Nature communications, 2020)
COVID-19 is associated with 5.1% mortality. Although the virological, epidemiological, clinical, and management outcome features of COVID-19 patients have been defined rapidly, the inflammatory and immune profiles require definition as they influence pathogenesis and clinical expression of COVID-19. Here we show lymphopenia, selective loss of CD4+ T cells, CD8+ T cells and NK cells, excessive T-cell activation and high expression of T-cell inhibitory molecules are more prominent in severe cases than in those with mild disease. CD8+ T cells in patients with severe disease express high levels of cytotoxic molecules. Histochemical studies of lung tissue from one fatality show sub-anatomical distributions of SARS-CoV-2 RNA and massive infiltration of T cells and macrophages. Thus, aberrant activation and dysregulation of CD8+ T cells occur in patients with severe COVID-19 disease, an effect that might be for pathogenesis of SARS-CoV-2 infection and indicate that immune-based targets for therapeutic interventions constitute a promising treatment for severe COVID-19 patients. Immunophenotyping of patients with COVID-19 is ongoing, but much remains to be learned. Here the authors analyze 41 hospitalized patients with COVID-19 and show a higher degree of lymphopenia in various immune cell subsets as well as cytotoxicity and T cell inhibitory marker expression in severe cases compared with mild.